Systematic Review Factors that Affect the Occurrence of Stunting - Rahmah Pujianti; Ummi Kalsum; Dwi Noerjoedianto (Jurnal Sehat Indonesia (JUSINDO), 2026)
Stunting in children aged 24 to 59 months is a health issue related to parenting patterns, social conditions, and family habits in meeting children's needs. This research aims to describe the factors related to the occurrence of stunting based on a review of six field research articles published between 2020 and 2025. Systematic review was conducted by searching articles in PubMed, Google Scholar, and Science Direct databases using keywords "stunting", "factors", "children 24 to 59 months", “health”, and "economy" with inclusion criteria: journal articles from the last 5 years, full text, English/Indonesian language. The results found 6 articles that meet the criteria. The results show that the occurrence of stunting in children aged 24 to 59 months is related to the dynamics of family life, starting from parenting patterns, feeding habits, social conditions, to the household economic situation. The dynamics of family life, starting from parenting patterns, feeding habits, social conditions, to the household economic situation affects the occurrence of stunting in children aged 24 to 59 months.